أنواع اللام في الأحاديث النبوية الواردة في الباب الأول من كتاب بلوغ المرام (دراسة تحليليّة نحوية): The Types of the Preposition Lām in the Prophetic Hadiths Found in the First Chapter of Bulūgh al-Marām - A. Hawariah (Pusat Penelitian dan Pengabdian Masyarakat (P3M), Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2025)
The researcher presents this academic thesis on the usage of the Arabic preposition “lām” (ḥarf al-lām) in the chapter of Ṭahārah (purification) from the book Bulūgh al-Marām. The aim of the research is to help readers of Bulūgh al-Marām understand the various meanings and types of the preposition lām, as well as to analyze its usage specifically within the chapter on purification. The researcher collected several books and articles relevant to the topic and identified grammatical rules involving the letter lām in the chapter of ẓuhrah (midday purification) from Bulūgh al-Marām. The methodology employed in this research is library research, in which the researcher gathers data from a range of scholarly articles, journals, and books related to the subject. In the chapter of purification in Bulūgh al-Marām, there are eleven types of the lām particle found in fifty-six hadiths. These include: six instances of lām al-ikhtiṣāṣ (denoting specification), nine of lām al-tamlīk (denoting possession), two of lām resembling tamlīk, six of lām al-tablig (denoting conveyance), four lām meaning